Water gated contrast switching with polymer–silica hybrid nanoparticles. Issue 59 (8th July 2019) - Pellico, Juan; Ellis, Connor M.; Miller, Jack; Davis, Jason J.
Abstract : The polymeric capping of a paramagnetically doped MSN enables the generation of high T 1 MRI contrast which is highly pH responsive through a fully reversible change in polymer conformation. Abstract : Bioresponsive contrast agents can provide smart signaling in MRI. In wrapping pore functionalised Gd-DOTA mesoporous silica nanoparticles with pH-responsive poly(acrylic acid), exchange between pore and bulk water can be reversibly switched by local pH. The generated high contrast then exhibits a large amplitude switch in a manner relevant to environmentally responsive imaging.